Leadership Communication Bulding Relationships in Organizations - Paulino De Deus (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Entitled "Leadership Communication Building Relationships in Organizations" with the objective of understanding how Leadership Communication builds relationships in organizations, a qualitative descriptive approach applied in this study, focusing on understanding leadership communication building relationships in organizations, particularly characterizing leadership communication, leadership communication effectiveness, and leadership communication building relationships in organizations. Data collected in this study comes from literature such as communication journals. Communication, leadership, and organization are three different but inherent concepts existing in an organization. Effective leadership communication in an organization requires continuous communication, listening, encouragement, providing illustrative stories, simplifying messages, and acting firmly through actions. Leadership communication building relationships in organizations requires involvement, commitment from all individuals in the organization, and beyond effective communication, as the reality may not always align with the ideal communication practices within a leadership organization. Leadership communication occurs through formal communication networks via official channels within the organizational hierarchy or position-based functions, consisting of downward communication (authority level high to authority level low) and upward communication (authority level low to authority level high) Efforts must be made to develop positive behavior among employees or members, thereby supporting the achievement of organizational objectives through effective communication, messaging, and situational awareness. Training on leadership is necessary to develop conscious leaders who understand what is lacking within their team and how they can improve the organizational environment.